2021
DOI: 10.1364/oe.434071
|View full text |Cite
|
Sign up to set email alerts
|

Permutation entropy analysis of the output of a laser diode under stimulated Brillouin scattering optical feedback

Abstract: The chaotic output emitted by a diode laser with optical feedback has fascinated the community for decades. The external cavity delay time imparts a weak level of periodicity to the laser output (the so-called "time delay signature", TDS) that is a drawback for applications that require random optical signals. A lot of efforts have focused in suppressing the TDS either by post-processing the signal or by using alternative ways to generate random optical signals. Here, we compare the signals generated by two op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The simplest method for weakening the TDS in an ECSL system is to decrease the feedback strength [22]. However, the complexity of the generated chaotic signal is relatively low under low feedback strength [23]. In order to solve this issue, one scheme based on two external cavities is proposed by adding another external cavity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest method for weakening the TDS in an ECSL system is to decrease the feedback strength [22]. However, the complexity of the generated chaotic signal is relatively low under low feedback strength [23]. In order to solve this issue, one scheme based on two external cavities is proposed by adding another external cavity.…”
mentioning
confidence: 99%
“…Through mapping the TDS in the parameter space of the bias current and the feedback strength, the optimized parameter region for generating chaotic signals with TDS below 0.1 is determined. Moreover, via the permutation entropy (PE) to analyze the complexity of the generated chaotic signal [23], the complexity of the chaotic signal does not decrease while the TDS is successfully concealed.…”
mentioning
confidence: 99%
“…Optical chaos generated by semiconductor lasers (SLs) has attracted much attention because of its potential applications of chaos-based communications [1][2][3][4], ultrafast random generation (RNG) [5][6][7], compressive sensing [8], neuro-inspired signal processing [9] and chaotic radar/laser radar (LIDAR) [10,11]. Studies have shown that SLs could exhibit rich dynamics under external perturbations [12][13][14][15][16][17], including, but not limited to, conventional optical feedback, frequency selecting feedback, filtered optical feedback, opto-electronic feedback and current modulation.…”
Section: Introductionmentioning
confidence: 99%